2017
DOI: 10.3390/hydrology4010005
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variability of Potential Evaporation across North American Forests

Abstract: Given the widespread ecological implications that would accompany any significant change in evaporative demand of the atmosphere, this study investigated spatial and temporal variation in several accepted expressions of potential evaporation (PE). The study focussed on forest regions of North America, with 1 km-resolution spatial coverage and a monthly time step, from 1951-2014. We considered Penman's model (E Pen ), the Priestley-Taylor model (E PT ), 'reference' rates based on the Penman-Monteith model for g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 70 publications
(96 reference statements)
3
12
0
Order By: Relevance
“…Similarly, parts of the Michigan Upper Peninsula and Northeast United States also show low trueâ0.25emvalues, which is due to increased number of waterbodies within SMAP pixels—These regions are excluded in further analysis. Nonetheless, the spatial pattern and distribution of 3‐year averaged trueâ from high in the southwest to lower in the Midwest as well as its dynamics range (~3–12 mm/day) is consistent with recent multidecade warm‐season Penman, Priestley‐Taylor, and pan‐evaporation analysis by (Hember et al, ). Other regional patterns for trueâ are also observed, such as lower values near the Mississippi embayment (<3 mm/day) as well as larger values (>10 mm/day) in the southeast.…”
Section: Resultssupporting
confidence: 86%
“…Similarly, parts of the Michigan Upper Peninsula and Northeast United States also show low trueâ0.25emvalues, which is due to increased number of waterbodies within SMAP pixels—These regions are excluded in further analysis. Nonetheless, the spatial pattern and distribution of 3‐year averaged trueâ from high in the southwest to lower in the Midwest as well as its dynamics range (~3–12 mm/day) is consistent with recent multidecade warm‐season Penman, Priestley‐Taylor, and pan‐evaporation analysis by (Hember et al, ). Other regional patterns for trueâ are also observed, such as lower values near the Mississippi embayment (<3 mm/day) as well as larger values (>10 mm/day) in the southeast.…”
Section: Resultssupporting
confidence: 86%
“…However, results from the Mekong Basin demonstrated that sunshine duration hours were the dominant factor contributing to ET 0 (B Li et al, 2015), while wind speed and RH were the most and least sensitive climatic factors for ET 0 in Malaysia, respectively (Askari et al, 2015). Similar to these results, a study of North American forests also showed that aerodynamic conditions were highly sensitive to ET 0 and that the PM model may overestimate the increase in evaporative demand (Hember et al, 2017). In China, a study based on the national average found that the most sensitive factor for ET 0 was the actual vapor pressure, followed by the daily maximum temperature and global radiation .…”
Section: Possible Reasons For the Energy Balance Closure Problemmentioning
confidence: 65%
“…Warm‐season soil water content was calculated from a monthly surface water balance model (Hember et al, ; Hember, Kurz, & Coops, ). The model followed previous implementations of Thornthwaite's initial approach (Willmott et al, ), only replacing the temperature‐based model of actual evapotranspiration with the Penman‐Monteith equation for forest canopies with moderate atmosphere‐canopy coupling (Hember, Coops, & Spittlehouse, ). Values for each tree were derived from the nearest cell within a 1‐km grid.…”
Section: Datamentioning
confidence: 99%